uantitative characterization of turbidity by radiative transfer based reflectance imaging - Hu, Xin-Hua; Tian, Peng; Chen, Cheng; Jin, Jiahong; Hong, Heng; Lu, Jun Q. (My University, 2018)
A new and noncontact approach of multispectral reflectance imaging has been developed to inversely determine the absorption coefficient of μ a , the scattering coefficient of μs and the anisotropy factor g of a turbid target from one measured reflectance image. The incident beam was profiled with a diffuse reflectance standard for deriving both measured and calculated reflectance images. A GPU implemented Monte Carlo code was developed to determine the parameters with a conjugate gradient descent algorithm and the existence of unique solutions was shown. We noninvasively determined embedded region thickness in heterogeneous targets and estimated in vivo optical parameters of nevi from 4 patients between 500 and 950nm for melanoma diagnosis to demonstrate the potentials of quantitative reflectance imaging.
Keywords: Reflection; Imaging systems; Spectroscopy; tissue diagnostics; Multiple scattering